Evaluasi Pelaksanaan Inspeksi Sanitasi Madrasah Al Munawwaroh di Kecamatan Kembangbahu Kabupaten Lamongan - Muhammad Hanif; Rizky Rahadian W; Gading Wilda Aniriani; Eko Sulistiono; Marsha Savira Agatha P; Nur Latifah Syakbanah; Denaya Andrya P (Jurnal Pemberdayaan Masyarakat, 2024)
School is a social interaction system of an entire organization consisting of personal interactions linked together in an organic relationship. It was observed that many of the quality of school buildings and sanitation facilities in Kembangbahu Lamongan Village did not meet environmental health requirements. So it becomes a factor causing disease and even transmission of disease between students or teachers at school. The aim of this research is to analyze the health quality of the school environment and health complaints at Madrasah Al Munawwaroh Kembangbahu Lamongan according to the Republic of Indonesia Minister of Health Decree No. 1429/2006. This research was conducted descriptively about a situation objectively. The population of this study was the total number of Al Munawwaroh Madrasah in Kembangbahu Village, by applying a total sampling technique of 3 school. Data analysis used the School Environmental Health Inspection Form modified from Minister of Health Decree No. 1429/2006 is then calculated using a formula and analyzed and then presented descriptively. The research results show that the majority of schools meet the requirements for location, building construction, building space, room air quality, lighting, ventilation, noise, school sanitation facilities, sports and worship facilities, courtyards and the presence of mosquito larvae